Increasing affective distance - leftward prism adaptation amplifies alexithymia in healthy females - Culicetto, Laura; Mucciardi, Massimo; Lucifora, Chiara; Falzone, Alessandra; Tomaiuolo, Francesco; Quartarone, Angelo; Vicario, Carmelo Mario; Schintu, Selene (Frontiers in Psychology, 2025)
IntroductionEmotional processing is linked with spatial attention, which prioritizes emotional stimuli over neutral ones. The interconnection between spatial and emotional processing may rely on the overlap between the networks underpinning such cognitive functions. Recent evidence has indeed identified a link between the rightward visuospatial bias exhibited by healthy individuals and the challenge in understanding emotional states, so-called alexithymia. However, while spatial attention has been manipulated by prism adaptation (PA), a well-known sensorimotor training, whether this is possible with emotional processing has never been investigated.MethodsNinety-five participants completed alexithymia questionnaires, Toronto Alexithymia Scale (TAS-20) and Perth Alexithymia Questionnaire (PAQ), before and after a single session of either leftward or rightward deviating PA.ResultsWhile both males and females showed the expected sensorimotor aftereffect solely leftward PA modulated alexithymia scores, and it did so only for women. The results indicate that leftward PA not only affects visuospatial performance, but also emotional processing, particularly in how individuals perceive and interpret emotional proximity and distance.DiscussionAlexithymia may be, therefore, metaphorically linked to impaired perception of emotional closeness and remoteness. These findings suggest that PA may modulate emotional capacities in a sex-dependent manner, offering insights into its therapeutic potential while also highlighting the need for caution as prolonged PA-based interventions may affect emotional well-being.